The Encyclopedia of Applied Linguistics 2012
DOI: 10.1002/9781405198431.wbeal0551
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Approach in Second Language Acquisition

Abstract: The interaction approach to second language acquisition posits that learners can benefi t from taking part in interaction because of a variety of developmentally helpful opportunities, conditions, and processes which interaction can expose them to. These include input, negotiation, output, feedback, and attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 28 publications
2
118
0
3
Order By: Relevance
“…Research has repeatedly shown that not only is provision of CF effective for language learning in general (Li, 2010;Lyster & Saito, 2010;Mackey & Goo, 2007;Russell & Spada, 2006), but also that learners overwhelmingly expect to receive information about how well they express themselves when speaking in a second/foreign language (e.g., Cathcart & Olsen, 1976;Chenoweth et al, 1983;Jean & Simard, 2011;Oladejo, 1993;Schulz, 1996Schulz, , 2001. Moreover, there is evidence that learners of different proficiencies tend to differ in the types of CF strategies they prefer and see as beneficial.…”
Section: Sources Of Reported Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has repeatedly shown that not only is provision of CF effective for language learning in general (Li, 2010;Lyster & Saito, 2010;Mackey & Goo, 2007;Russell & Spada, 2006), but also that learners overwhelmingly expect to receive information about how well they express themselves when speaking in a second/foreign language (e.g., Cathcart & Olsen, 1976;Chenoweth et al, 1983;Jean & Simard, 2011;Oladejo, 1993;Schulz, 1996Schulz, , 2001. Moreover, there is evidence that learners of different proficiencies tend to differ in the types of CF strategies they prefer and see as beneficial.…”
Section: Sources Of Reported Beliefsmentioning
confidence: 99%
“…Corrective feedback plays an important role in the language acquisition process (Li, 2010;Lyster & Saito, 2010;Mackey & Goo, 2007;Russell & Spada, 2006). Specifically, CF allows teachers to provide information about the accuracy of learners' production by raising awareness of the formal aspects of an L2 in the input.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cooperative learning methods, which differ from traditional learning methods, have some benefits resulting from social interaction between students (Levine, 2002). Classroom social interaction, according to Mackey (2007) and Ellis (2003), is beneficial to overall language development. It has been observed that students who interact and speak achieve better in oral skills in most cases than those who always keep silent (Khadidja, 2010).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Presenting a good speaking lesson is depending on the interaction between teachers and students, students and students, between students and materials. Fluency and accuracy are main characteristics approach in the communicative approach of language teaching [33,34].…”
Section: Components Of Classroom Interactionmentioning
confidence: 99%